Clostridium ramosum rapidly identified by MALDI-TOF MS. A rare gram-variable agent of bacteraemia. Issue 8 (15th August 2020) - Legaria, M.C.; García, S.D.; Tudanca, V.; Barberis, C.; Cipolla, L.; Cornet, L.; Famiglietti, A.M.R.; Stecher, D.; Vay, C.A.
Abstract : Clostridium ramosum is an enteric anaerobic, endospore-forming, gram-positive rod with a low GC content that is rarely associated with disease in humans. We present a case of C. ramosum bacteraemia. To the best of our knowledge, this is the second case of C. ramosum bacteraemia in an elderly patient presenting with fever, abdominal pain and bilious emesis. We highlight the Gram stain variability, the lack of visualization of spores and the atypical morphology of the colonies that showed C. ramosum in a polymicrobial presentation that initially appeared to show monomicrobial bacteraemia. The microorganism was rapidly identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). We present a comprehensive literature review of 32 cases of clinical infections by C. ramosum in which we describe, if available, sex, age, clinical symptoms, predisposing conditions, other organisms present in the blood culture, other samples with C. ramosum, identification methodology, treatment and outcome.